Salmonella induced abortion storm in donkeys at tropical southern agroclimatic zone of Tamil Nadu - N R, BHATHRA; R, MANIKANDAN; V, PRABAHARAN; S, GANESH KUMAR; A, GANESAN; A, SABARINATHAN (The Indian Journal of Animal Sciences, 2024)
A commercial donkey farm at Tirunelveli with 323 pregnant donkeys was facing an abortion storm affecting 53 (16.4%) pregnant jennies in the last trimester, which were presented to LAC-OP-OG unit of Veterinary Clinical Complex, Veterinary College and Research Institute, Tirunelveli. Clinical examination revealed pyrexia (39.4℃) and congested conjunctival mucous membrane. Gynaecological examination revealed oedematous vulva with serosanguinous vaginal discharge. Ultrasonography examination revealed the presence of corpus luteum, medium-sized follicles, thickened uterine endometrium and fluid accumulation at the tip of both uterine horns. Serum progesterone and cortisol levels were 5.35±0.28 ng/mL and 6.14±0.13 ng/mL, respectively. Microbiological examination of foetal fluids revealed gram-negative bacilli which was confirmed as Salmonella spp. Histopathology of aborted foetal parts revealed cellular degenerative changes. All jennies were treated with antibiotics, and antihistamines along with intrauterine douching for five consecutive days. Other pregnant jennies in the farm were isolated and prophylactic antibiotics and immune booster supplements were administered. Thus, this study documented unconventional infectious agent such as Salmonellosis emerging as a leading cause of abortion storm and reproductive loss in donkey farming in Tamil Nadu.